How Interior Design Impacts Learning Performance for Children with Special Needs in Surabaya - Valentine Vallery Haryanto; Laksmi K. Wardani; Felicia Wagiri (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2023)
According to Indonesia’s Central Statistics Agency (BPS), the number of children with special needs in 2017 reached 1.6 million, and among them, only 18% received inclusive education services. The Surabaya Government has issued a policy that every school has an inclusion class to accommodate children with special needs. Many factors determine the growth and development of children, such as formal and informal education. Therefore, equity in education for children is a crucial topic to study. Since all children should receive proper educational facilities to maximize their potential, interior design can be a solution to convey an adequate learning environment for children with special needs. Thus, this paper will survey children with special needs concerning school design planning using interactive and non-interactive qualitative data collection methods, including literature focusing on behavioral characteristics related to the environment, interviews, observation, and visits to some appropriate sites. The survey will be conducted with at least 40 respondents, including parents, teachers, and peers of the children. The goal of this study is to provide suggestions to schools around Surabaya on how to make their education more inclusive.